PENGARUH RESIKO EKONOMI TERHADAP PENANAMAN MODAL ASING DI NEGARA ASEAN (STUDI KASUS PERBANDINGAN ANTARA NEGARA INDONESIA, MALAYSIA, SINGAPURA, THAILAND, FILIPPINA, BRUNEI DAN MYANMAR) - Alghifari Mahdi Igamo (Department of Development Economics, Universitas Sriwijaya, 2015)
The objective of this research was to investigate and analyze the Effect of Economic Risks on Foreign Investment in ASEAN countries (A Comparative Case Study among the Countries of Indonesia, Malaysia, Singapore, Thailand, the Philippines, Brunei and Myanmar). The method of analysis used in this study was the fixed-effect method. The research result showed that individually real GDP and foreign exchange reserves had a statistically significant positive influence on foreign investment in ASEAN countries in 2004-2013. The result of the same calculation process also showed that individually inflation and exchange rates did not have a statitiscally significant effect on foreign invesment in ASEAN countries in 2004-2013. Keywords: Foreign Investment, Real GDP, Inflation, Exchange Rates, Foreign Exchange Reserves